10 year review of low speed vehicle run-overs in 0–15 year olds across Queensland. (1st March 2011) - Kimble, R; Wallis, B; Nixon, J; Watt, K; Cass, D; Gillen, T; Griffin, B
Abstract : Transportation injury is the leading external cause of child deaths in Australia, and pedestrian deaths comprised approximately 25% of these over the last 4 years. There is evidence that the rate of low speed vehicle run-overs (LSVROs) in Queensland is significantly higher than the rest of Australia. Despite this, limited data are available on fatal and non-fatal LSVROs. There is no specific coding mechanism available to describe these events, resulting in inadequate description of the magnitude of the problem, the risk factors associated with LSVROs, and the associated morbidity and mortality. Epidemiological surveillance of both fatal and non-fatal LSVROs is essential to understand and describe the burden of injury. The purpose of this study is to determine the incidence of fatal and non-fatal LSVRO events among 0–15 year olds in Queensland from 1999 to 2008, to determine risk factors that can inform injury prevention strategies. A major outcome of this study is to develop a reliable system of surveillance to readily identify these events, and allow routine monitoring. Retrospective (1999–2008) data were obtained on all fatal and non-fatal LSVROs among 0–15 year olds in Queensland. Data were obtained and linked from multiple sources (prehospital, Emergency Department, Admitted Patients, Coroners), and supplemented by injury surveillance, to allow investigation of incidence, trends, risk factors, mechanisms and vehicle types. Preliminary analyses indicate that there were 19 deaths (13 boys and 5 girls, 1 unknown) from LSVROs between 2004 and 2009 in Queensland. Approximately half of these deaths occurred in children aged 0–2 years (n=10; 53%). The majority of incidents occurred on private property. A four wheel drive vehicle was involved in almost half of these fatalities (n=11; 58%), and large family sedans accounted for four out of 19 fatalities. Data on nonfatal LSVROs are currently being collated. Additional analyses will be performed to determine whether the patterns are similar to those observed among fatal incidents. Comprehensive secular data on LSVROs are currently not available. This study is designed to obtain these data, and establish a prospective surveillance of LSVROs, ultimately reducing associated burden of injury.